2014
DOI: 10.1039/c4ra01425a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic exploitation of halogenated alkenes containing EWG: benzotriazole-mediated synthesis of benzoazetines and thermal transformations

Abstract: The stable benzoazetines (5a–d) based on nitrovinyl moieties have been synthesizedviatransamination of bisbenzotriazolyl derivatives (2a–c).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, in addition to the TBAF-assisted process mentioned above, only one example of anti-Michael 5- endo-dig hydroamination of an alkynoate ester has been reported; and in that case, the cyclization was favored by the particular structure of the substrate, possessing a crowded quaternary center ( gem -dimethyl effect). Alternatively, Michael-type cyclization of 3 , affording a strained benzazetine ring, could also be possible, at least in principle: one example of 4- exo-dig Pd-catalyzed intramolecular hydroamination of gem-difluoropropargylamides has been described, and the formation of the β-lactam ring was driven by the polarization of the triple bond induced by fluorine substituents. Moreover, we have recently reported that, in the presence of cationic Au­(I) complex (JonPhosAuNCMe)­SbF 6 , substrates 3 underwent a sequential reaction, affording eight-membered dibenzo­[1,5]­diazocines 5 (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, in addition to the TBAF-assisted process mentioned above, only one example of anti-Michael 5- endo-dig hydroamination of an alkynoate ester has been reported; and in that case, the cyclization was favored by the particular structure of the substrate, possessing a crowded quaternary center ( gem -dimethyl effect). Alternatively, Michael-type cyclization of 3 , affording a strained benzazetine ring, could also be possible, at least in principle: one example of 4- exo-dig Pd-catalyzed intramolecular hydroamination of gem-difluoropropargylamides has been described, and the formation of the β-lactam ring was driven by the polarization of the triple bond induced by fluorine substituents. Moreover, we have recently reported that, in the presence of cationic Au­(I) complex (JonPhosAuNCMe)­SbF 6 , substrates 3 underwent a sequential reaction, affording eight-membered dibenzo­[1,5]­diazocines 5 (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%